Analisis Penyusunan Standar Operasional Prosedur Teaching Factory Eduwisata Politeknik Negeri Jember - Dzulkifli, Muhammad; Milawaty Milawaty; Utami, Lely Dian; Samsudin, Asep (Pusat Penelitian Dan Pengabdian Masyarakat STIEPARI Semarang, 2023)
This research aims to develop Standard Operating Procedures (SOP) for Governance and Service Activities for TEFA Edutourism Polije. SOP development is one of the eight requirements in the effort to establish TEFA Edutourism Polije. The method used in this research is descriptive qualitative with data collection using observation, interviews, FGD, documentation and literature study. Activities carried out in this research include identifying Edutourism activities, identifying stakeholders, as well as identifying tasks and work procedures at TEFA Edutourism Polije. The main activity in Edutourism consists of visits to several TEFAs developed in Polije. The parties involved include Public Relations, the Integrated Agricultural Academic Services Unit (UPA) and the Food Product Development, Management and Packaging Academic Services Unit (UPA) which manages various TEFAs at Polije. The results of this research are, Administrative SOPs and TEFA Edutourism Polije Service SOPs. It is hoped that the SOP created can support the development of TEFA Edutourism Polije.